The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1111/j.1540-8159.1996.tb03225.x
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Induced Sympathetic Influences Do Not Change Interatrial Conduction Times in VDD and DDD Pacing

Abstract: Using telemetry, right atrial electrogram (RA), and marker channel of atrial sense events (MA) in combination with the left atrial electrogram (LA), recorded by a filtered bipolar esophageal lead, interatrial conduction during submaximal exercise and at rest was examined in 46 DDD pacemaker patients. The RA-LA and MA-LA conduction times measured in the presence of atrial sensing (VDD) as well as the conduction time SA-LA from atrial stimulus (SA) to LA, determined during atrial pacing (DDD) were found to be in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Therefore, our results do not support its use during atrial pacing. Ismer et al 10 investigated IACT during exercise‐induced changes in sinus rate and reported no effect of sympathetic influences on IACT. However, since increased sympathetic tone is known to shorten intrinsic atrio‐ventricular conduction, RAAV may be still appropriate for maintaining biventricular capture during increased atrial sensed rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, our results do not support its use during atrial pacing. Ismer et al 10 investigated IACT during exercise‐induced changes in sinus rate and reported no effect of sympathetic influences on IACT. However, since increased sympathetic tone is known to shorten intrinsic atrio‐ventricular conduction, RAAV may be still appropriate for maintaining biventricular capture during increased atrial sensed rate.…”
Section: Discussionmentioning
confidence: 99%
“…The atrioventricular delay (AV) programmable in the device defines the electrical delay between the right atrial activation and ventricular pacing and, generally speaking, is different from the mechanical delay between the left atrial and left ventricular contractions. Several patient‐specific factors, such as conduction between the right and left atria as well as electro‐mechanical coupling, are responsible for this difference 9–11 . The optimal device AV delay can be determined by either accounting for these factors 12 or, alternatively, by iterating through a number of device settings and evaluating cardiac function at each.…”
Section: Introductionmentioning
confidence: 99%
“…During healthy ventricular conduction or simultaneous biventricular pacing, the left AV interval is shorter than the right AV interval due to the interatrial conduction time (IACT). It seems that exercise does not change mean IACT in subjects without HF 9 or in patients with CRT 10 . However, incremental atrial pacing in the absence of sympathetic nerve stimulation increased IACT by >10 ms in 57% of a not further specified population with dual chamber pacemaker 11 .…”
Section: Physiologic Background Of Av Delay Programmingmentioning
confidence: 91%
“…Intracardiac electrogram studies in patients with pacemakers for bradycardia indications have shown that increases in heart rate have no influence on IACT, in both atrially paced and atrially sensed modes . An invasive study suggested that IACT is not changed by exercise in CRT patients …”
Section: Discussionmentioning
confidence: 99%